1982
DOI: 10.1002/jat.2550020307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorine and monochloramine in drinking water on the developing rat fetus

Abstract: Chlorine dioxide (C102) or monochloramine (NH2C1) may be considered as an alternative to chlorine (HOCl) as a disinfectant in public water supplies, since chlorination produces trihalomethanes. This study was conducted to determine the effect of chlorine and monochloramine on rat fetuses. Female rats were administered 0, 1, 10 or 100 mg 1-I NHzCl or HOCl daily in the drinking water for 23months prior to and throughout gestation. Rats were sacrificed on Day 20 of gestation and fetuses were preserved for soft-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, it has to be clear that there is no epidemiological data suggestive of a carcinogenic effect of these compounds. Many reports showed that chlorinated disinfectants can be very irritant to the skin and mucous membranes (Dakin, 1915;Brennan and Leaper, 1985), others showed a mutagenic effect on animal tissues (Kawachi et al, 1980) and teratogenesis (Abdel-Rahman et al, 1982). Nevertheless, one has to recall that the above studies have all employed high concentrations of these compounds far beyond the safety limits allowed for human usage, and for relatively short periods of time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be clear that there is no epidemiological data suggestive of a carcinogenic effect of these compounds. Many reports showed that chlorinated disinfectants can be very irritant to the skin and mucous membranes (Dakin, 1915;Brennan and Leaper, 1985), others showed a mutagenic effect on animal tissues (Kawachi et al, 1980) and teratogenesis (Abdel-Rahman et al, 1982). Nevertheless, one has to recall that the above studies have all employed high concentrations of these compounds far beyond the safety limits allowed for human usage, and for relatively short periods of time.…”
Section: Resultsmentioning
confidence: 99%
“…Similar tests using human embryo fibroblasts showed aberration in sister chromatid exchange tests. Interaction of halogenated compounds and nucleic acids (Olivieri et al, 1978) and teratogenesis in the developing rat foetus (Abdel-Rahman et al, 1982) have been reported. Short-term and long-term bioassay studies on the carcinogenicity of sodium hypochlorite in F344 rats (Hasegawa et al, 1986) demonstrated an increasing incidence in both benign and malignant neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that monochloramine exposure did not harm female fertility, reproductive organs, pup weight or litter size in rats [ 31 ]. Additionally, neither teratogenic nor embryotoxic effects of monochloramine have been found in animal studies [ 32 ]. To our knowledge, there have been no recent studies on the health risks of chloramine.…”
Section: Discussionmentioning
confidence: 99%
“…Testing the oxidation potential and mutagenicity of NaOCl has a long history, due its use as the main disinfectant for drinking water [ 119 ], [ 120 ], [ 121 ]. As early as 1997, Soffritti et al reported the results of long-term carcinogenicity bioassays (104 weeks) on chlorine (in the form of sodium hypochlorite and monochloramine in increasing doses from 0, 70, 140, to 275 ppm), administered in drinking water to rats and mice.…”
Section: Safety – Hocl Tissue Compatibility and Tolerancementioning
confidence: 99%